Comparative analysis of RAD-seq methods for SNP discovery and genetic diversity assessment in oil seed crop safflower - Pooja Pathania; Gaddam Prasanna Kumar; Nishu Gupta; R. Parimalan; J. Radhamani; Rajesh Kumar; Sunil Shriram Gomashe; Palchamy Kadirvel; S. Rajkumar (Scientific Reports)
Abstract Safflower (Carthamus tinctorius L.) is an important oilseed crop with diverse uses and the potential for genetic improvement. This study aimed to optimize genotyping-by-sequencing (GBS) for safflower via in silico and in vitro methods with two restriction site-associated DNA sequencing (RAD-seq) approaches, i.e., single restriction site-associated DNA sequencing (sdRAD-seq) and double-digest RAD sequencing (ddRAD-seq) and three restriction enzyme combinations (ApeKI, NlaIII_Msel, and EcoRI_Msel). Forty-two safflower accessions were selected for this study. In silico testing revealed that NlaIII_Msel generated the largest number of DNA fragments, followed by ApeKI and EcoRI_Msel. The in vitro results showed that ddRAD-seq outperformed sdRAD-seq in terms of raw read count, alignment rate, depth and breadth of coverage, and SNP detection. An alignment-free analysis using k-mer counting and sketching based on genetic distance further confirmed the superiority of ddRAD-seq. Gene-level k-mer validation identified more core genes in the ddRAD-seq data. Variant calling resulted in 6,721, 173,212, and 221,805 single nucleotide polymorphic sites (SNPs) for ApeKI, NlaIII_Msel, and EcoRI_Msel, respectively. SNP annotation and distribution analysis revealed that EcoRI_Msel captured more SNPs with fewer missing observations. Principal component analysis via ddRAD-seq data explained 30.29% and 33.98% of the total genetic variation in NlaIII_Msel and EcoRI_Msel, respectively. This study demonstrated that ddRAD-seq with the EcoRI_Msel enzyme combination is the most suitable GBS approach for genome sampling and SNP genotyping in safflower.